Worksheets Electronic Development of STEAM-Based to Improve Students' Creative Thinking Ability - Deden Dicky Dermawan; Kinanti Andartiani (Program Studi Tadris Matematika IAIN Salatiga, 2022)
This study aimed to develop a valid, practical, and effective STEAM-based E-LKPD to improve students' creative thinking skills. This study used research and development procedures with reference to the 4D model (Define, Design, Develop, and Disseminate) but this research is only up to the develop stage. The experimental design used is